The Impact of Quality Management (Soft and Hard Aspect) on Innovation Performance by Mediating Role of Technological Innovation Capability and Proactive Behaviour, (The Case: Knowledge-Base Firms) - Mojtaba Rezaei Zivlaei; hesam zandhesami (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2020)
The related researches show different results from the relationship between aspects of quality management and innovation performance. Most researches examined the direct relationship between quality management and organizational innovation performance, but the effective aspects of quality management have not been thoroughly investigated, so the present study considered clarifying the aspects of quality management and their impacts on organizational innovation performance. The purpose of this study is to investigate the impact of soft and hard aspects of quality management on innovation performance by mediating the role of employees' proactive behavior and technological innovation capability. Because the current situation has been studied and analyzed in this applied research, the method used is analytical-survey. The statistical population of this study are 400 knowledge-based companies in the field of laboratory equipment and materials manufactured in Iran who participated in the 6th exhibition of this field at Tehran International Exhibition. Theoretical bases were used to collect the relevant data, as well as to extract primary factors and indices from library and internet resources including articles, books and case studies. Also, during the process of attending the exhibition, questionnaires were used to collect the data and information needed to investigate the research hypotheses. Inferential statistics indices were determined and extracted according to the desired dimensions. After checking the validity and reliability of the questionnaire, the data normality test was performed using Kolmogorov-Smirnov test, then we analyzed the hypotheses using Structural Equation Modeling and SmartPLS and SPSS software. The results show that 5 hypotheses out of 8 proposed hypotheses were confirmed and it was found that soft quality management mediated by innovation capability and proactive behavior of employees had significant effect on innovation performance and hard quality management had significant effect on innovation capability. Also, innovation capability significantly affects the innovation performance of the organization.